Persepsi Perawat Terhadap Penilaian Nyeri Pada Pasien Di IGD RSUD Dr. T. C. Hillers Maumere - Yunita Trisna; Ode Irman; Yuliani Pitang (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Pain is a complex phenomenon as a psychological experience. Inaccurate pain assessment results in inappropriate pain management. Inappropriate pain appraisals are associated with perception. The aim of the research is to explain the correlation between nurses' perceptions of patients' pain assessments. The type of research is observational research, with a cross sectional approach. This research involved 60 respondents (30 nurses and 30 patients) taken using quota sampling and carried out in November 2023 at RSUD dr. T.C. Hillers Maumere. The instrument used to measure perceptions uses a questionnaire that has been tested for validity and reliability. The r value>0.4438 and Cronbach's alpha value 0.893. Pain assessment was measured using standard operating procedures (SOP). Data were analyzed using the contingency coefficient test. The research results showed that 56.7% had negative perceptions and 80% of nurses carried out pain assessments that did not comply with the SOP. The results of the contingency coefficient test obtained a value of p = 0.067 (p > 0.05), so there is no relationship between nurses' perceptions of pain assessment in patients in the emergency department. This research concluded that the majority of nurses' perceptions were negative perceptions and the highest assessment of pain was that it did not comply with the SOP. In addition, there was no relationship between nurses' perceptions of patients' pain assessments. For this reason, nurses must carry out pain assessments according to existing SOPs.